Pre-germinative treatments for seed dormancy breaking of three populations of Ramorinoa girolae, an endemic woody species from arid zones in Argentina - Zapata, Ricardo M; Malo, Carmen Azagra; Karlin, Marcos S (BOSQUE, 2017)
For the conservation of species, especially those endemic or vulnerable, it is necessary to deepen the knowledge about their ecological dynamic and to find adequate techniques for multiplication. Ramorinoa girolae, “chica”, is an endemic woody species of the xerophytic flora from western Argentine arid regions, with a restricted occupation area and fragmented communities. The lack of records makes relevant the conduction of research underpinning knowledge of the species, regeneration mechanisms and multiplication techniques. The objective of this work was to study the behavior of seeds of three populations under germination conditions and the response for different pre-germinative treatments. Germination trials were made in the laboratory with different pre-germinative techniques using the seeds of three populations under a completely aleatory design. Results confirm the presence of physical dormancy in seeds restricting the imbibing process for their rapid germination. The treatments, hot water scarification and mechanical scarification with sandpaper, increase significantly the germination percentages. The best treatment is mechanical scarification with sandpaper, reaching values of 92 % of germination at five days from the beginning of the treatment. The uneven response of germination of the different populations confirms the different behavior of local populations and results interesting for ecosystem studies and future lines of investigation and management of this species. These technical aspects appear as relevant for the application of reforestation and environmental restoration programs.